Pemanfaatan Aplikasi MiMind dalam Meningkatkan Pembelajaran Menulis Puisi Ode Bertema Tokoh Cianjur - Dede Susilawati; Siti Maryam; Aprilla Adawiyah (Universitas Suryakanca, 2025)
This article to describe the utilization of MiMind application in improving the learning outcomes of writing ode poetry in class XI students of MAN 1 Cianjur. The research method used was an experiment with a One-Group Pretest-Posttest design, The results showed a significant improvement in the ability to write ode poetry after using MiMind application, especially in the aspects of theme, diction and imagery. This can be seen from the increase in students' average scores, from 50.55 in the initial test (pretest) to 88.88 in the final test (posttest). The Wilcoxon hypothesis test obtained an Asymp. Sig. (2-tailed) 0.00 (